An optimal risk – return portfolio of Islamic banks. Issue 4 (4th November 2014) - Alam Choudhury, Masudul; Ismal, Rifki
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to analyze individual financing instruments and portfolios of instruments, and find the location of the most efficient portfolio financing. The Indonesian Islamic banking industry is very promising with four dominant financing instruments, namely, Mudarabah, Musharakah, Murabahah and Istishna. Each instrument has unique pattern of return, expected return and risk. Moreover, the variances of two, three and four financing instruments suggest the importance of identifying the most prospective financing instruments. Further, the most efficient portion of the most prospective financing is determined by constructing an efficient portfolio financing frontier. Design/methodology/approach – Technically, it uses risk and return theory to compute risk, return and variance of an instrument and set of financing instruments. In addition, it uses an efficient portfolio frontier curve to locate all combination of the most progressive portfolio financing and finds the most efficient portfolio financing. Findings – It finds some interesting finding with regard to the pattern of return, characteristics of a financing instrument and groups of financing instruments. The most essential finding of the paper is the location of the most efficient portfolio financing. Research limitations/implications – The information and finding of this paper benefit the Indonesian Islamic banking industry to optimize the performance of an individual and groups of financing instruments. Particularly, for the most progressive financing instruments, it proposes the combinations of portfolio financing which give optimum output. Originality/value – To the best of author's knowledge, this is the first paper trying to analyze and construct an efficient portfolio financing frontier of the Indonesian Islamic banking industry.